The EU budget dispute :a blessing in disguise? - Ondřej Schneider (Center for Economic Studies and ifo Institute (CESifo), 2007)
This paper analyses the European budget and the position of the ten new member states. We argue that the EU budget should be reconsidered, as the Union has expanded to 27 member states and has become more heterogeneous. The budget priorities must be re-oriented towards potentially productive spending programmes. A simple economic growth model illustrates that the current EU budget setting is, at best, neutral with respect to the EU-wide long-term growth potential and may actually hamper growth in the majority of the EU countries if the distortionary nature of taxation is taken into account.
Keywords: E6; H77; 330; Öffentlicher Haushalt; Finanzpolitik; Wirtschaftswachstum; Schätzung; EU-Staaten